Electrical and optical characteristics of capacitors based on nanocomposite material GASE <KNO3> - Ковалюк, Захар Дмитрович; Нетяга, Віктор Васильович; Коноплянко, Денис Юрійович; Бахтінов, Анатолій Петрович (Eastern-European Journal of Enterprise Technologies, 2010)
Impedance spectra of the GaSe nanostructures are investigated under illumination. It is established that the processes of accumulation and transport of charge carriers in these structures are due to quantum-dimensional processes in high electrical fields. We have found an essential increase of the capacity of capacitors under their illumination.